Pluralisme Agama dan Modernitas Pembangunan: Rekonstruksi Pemikiran Pluralisme dalam Membentuk Etika Universal - burhanudin mukhamad faturahman (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
Social conflict that occurred in Indonesia with a religious background is very concern. Religious pluralism should be the yardsticks religious tolerance in the midst of diversity, tolerant attitude of trust with fairness in order toward a civil society. In addition modernity allegedly subverts the social order because it creates an unfair economic system. The purpose of this writing to discuss religious pluralism with the value contained in it in terms of thinking Dawan Rahardjo, Nurcolish Madjid and John Hick with a contribution of modernity against the onset of social conflict. The research of religious pluralism in Indonesia namely according to Rahardjo addressed as a social integration as the Foundation behave because actual religions taught the values of public virtue while Madjid argued civil society is Home of democracy with an ethic of community as the quality of the life of democracy. Hick States pluralism as centering yourself towards the single reality of centering (of God) through different forms and ways. This diversity is vulnerable to conflict because of modernity triggered poverty, environmental destruction and communal violence. Therefore strengthening the education of multi religious and ethical global College absolutely implemented in an effort to create a civil society